1. Solve one of the equations for one of the variables (in this case, y = -4)
2. Substitute the value of the variable into the other equation (-7x - 2(-4) = 13)
3. Solve for the other variable (-7x + 8 = 13, -7x = 5, x = -5/7)
4. Check the solution by substituting the values back into both original equations (x = 3, y = -4)
Put the steps in order that are used to solve the following systems of equations by substitution.
(-7x
- 2y
=
13
x
2y
=
11
= y = −4
= −7 (2y+11) - 2y = 13
= (3,-4)
= -16y= 64
= x - 2y = 11 → x = 2y+11
= -16y 77: 13
=
= -14y-77 - 2y = -13
=
x =
= 2(-4)+11 → x = 3
Brainly Ginny character avatar
Brainly Ginny character avatar
1 answer